The Expression of Ki-67 and E-cadherin in Triple Negative Breast Cancer: A Hospital Based Study - Nishat, Latifa; Tanjin, Rokhsana; Arjuman, Farida; Yesmin, Zinnat Ara; Laboni, Umma Habiba; Amee, Samira Sultana (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Triple negative breast cancer (TNBC) is a subtype of breast cancer with aggressive nature as it does not respond to targeted chemotherapeutics. Expression of biomarkers is considered as an important factor for selecting treatment strategies and assessing prognosis. Objective: The aim of this study was to assess the expression of Ki-67 and E–cadherin in TNBC tissue. Methods: Immunohistochemical staining was done to assess the expression of proliferative marker Ki-67 and junctional complex marker E-cadherin in the Formalin Fixed Paraffin Embedded tissue (FFPE) of 80 TNBC patients. Ki-67 positive cells were identified on the basis of brown staining nuclei and E-cadherin expressed cells were considered positive on the basis of brown staining cell membrane. Ki-67 positive TNBCs were divided into low and high Ki-67 groups. Results: Ki-67 was expressed in 65% of the TNBC, the median of Ki-67 index was 30.25%. The difference between the medians of Ki-67 expression of low and high groups (7.5% and 53.25% respectively) was highly significant (p = 0.000). E-cadherin was negative in 67.5% of TNBC patients. The mean (±SD) age at diagnosis was 43.79 (±9.10) years. Most of the cancers were invasive ductal cell carcinoma (95%) and of grade II (70%). Lymph node metastasis was present in 73.8% patients and in 51% cases the cancer was in the left breast. Ki-67 expression was significantly associated with lymph node metastasis and E-cadherin expression was more negative in the left sided cancer. Conclusion: The study signifies that the TNBC has an early age at onset and Ki-67 expression is significantly high and associated with lymph node metastasis pointing the importance of this biomarker in TNBC patients. Negative expression of E-cadherin suggests close monitoring of the left sided TNBC.